"Subjectivity" as the foundation of metaphysics in Kant's transcendental philosophy - ali fathi (حکمت اسرا, 2021)
One of the serious questions in Kant's philosophical system is the question of the possibility of metaphysics; In his transcendental philosophy, Kant denies metaphysics on the one hand and proves it on the other. This paper has tried to refer to the various meanings of metaphysics in his view, using the meaning and subject of this knowledge in Aristotle and enumerating it. Some of its features, such as unity, comprehensiveness, and its fundamentality, are examined by Kant for another meaning of metaphysics, and show how, in spite of some misplaced narratives and interpretations by the Neokantians, he still thinks of existence of being in His philosophy has emerged as a subjective matter, and this is important with the help of imagination and in the transcendental schematism through time and its role in the possibility of synthesis between the two sides of the synthetic a priori judgment (ie pure intuition and pure concept) and the structural union between these two. That is, time as pure all-encompassing intuition and transcendent (pure) self has been done through the power of imagination, and the unity between the two aspects of acceptance and spontaneity has finally been established on the basis of subjectivity, which is mentioned in this article under the title of subjectivity.Keywords: Subjectivity, Pure Intuition, Transcendental Metaphysics, Transcendental ego, Schematism